Meiotic Chromosome Contacts as a Plausible Prelude for Robertsonian Translocations - Matveevsky, Sergey (Genes (Basel), 2020)
Robertsonian translocations are common chromosomal alterations. Chromosome variability affects human health and natural evolution. Despite the significance of such mutations, no mechanisms explaining the emergence of such translocations have yet been demonstrated. Several models have explored possible changes in interphase nuclei. Evidence for non-homologous chromosomes end joining in meiosis is scarce, and is often limited to uncovering mechanisms in damaged cells only. This study presents a primarily qualitative analysis of contacts of non-homologous chromosomes by short arms, during meiotic prophase I in the mole vole, Ellobius alaicus, a species with a variable karyotype, due to Robertsonian translocations. Immunocytochemical staining of spermatocytes demonstrated the presence of four contact types for non-homologous chromosomes in meiotic prophase I: (1) proximity, (2) touching, (3) anchoring/tethering, and (4) fusion. Our results suggest distinct mechanisms for chromosomal interactions in meiosis. Thus, we propose to change the translocation mechanism model from ‘contact first’ to ‘contact first in meiosis’.